To Achieve High-Quality Agricultural Development is the General Trend of the Times - Guo Zhongsheng (Journal of Plant Genetics and Crop Research, 2025)
Farming development has gone through a long process. After a review of literatures, the results showed that according to the efficiency of resource utilization by plants, the whole process of farming development can be divided into three stages, the whole process of farming development can be divided into three stages: Low level development stage or primitive farming, Level improvement stage and high-quality development new stage. The direction of Farming development is High-quality development. Farming High-quality development is to take some effective measures or methods to make land produce maximum yield and benefit to meet the people’s needs for a better life and safe food, which is the general trend of the times.
Keywords: Farming development